FINANCIAL MANAGEMENT OF SOCIAL AND ECONOMIC SYSTEMS - A. Ksenofontov (Publishing House of the State University of Management, 2017)
Based on the theory of systems the conceptual model of functioning of the budget Russian Federation system is offered. The budget system is considered as the big diffusion system consisting of 85 social and economic subsystems. The analysis of profitable and account parts of the consolidated budget Russian Federation is carried out. Also the conceptual model of financial and economical activity of the territorial subject of the Russian Federation is offered. Financial and economic activities of two territorial subjects of the Russian Federation are researched.